2013
DOI: 10.1073/pnas.1321511111
|View full text |Cite
|
Sign up to set email alerts
|

Rare event of histone demethylation can initiate singular gene expression of olfactory receptors

Abstract: Mammals sense odors through the gene family of olfactory receptors (ORs). Despite the enormous number of OR genes (∼1,400 in mouse), each olfactory sensory neuron expresses one, and only one, of them. In neurobiology, it remains a long-standing mystery how this singularity can be achieved despite intrinsic stochasticity of gene expression. Recent experiments showed an epigenetic mechanism for maintaining singular OR expression: Once any ORs are activated, their expression inhibits further OR activation by down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 35 publications
(42 reference statements)
1
34
1
Order By: Relevance
“…Thus, for most ORs, H3K9 demethylation is necessary but not sufficient for expression at high cellular levels. Although recent theoretical calculations support that a slow demethylation process combined with a fast feedback can explain singular OR expression (Tan et al, 2013), our experimental findings suggest that an additional regulatory layer may also contribute to the singularity of OR choice. Were the absence of H3K9 methylation sufficient for robust OR transcription, then most G9a/GLP KO OSNs should express multiple ORs at high levels.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Thus, for most ORs, H3K9 demethylation is necessary but not sufficient for expression at high cellular levels. Although recent theoretical calculations support that a slow demethylation process combined with a fast feedback can explain singular OR expression (Tan et al, 2013), our experimental findings suggest that an additional regulatory layer may also contribute to the singularity of OR choice. Were the absence of H3K9 methylation sufficient for robust OR transcription, then most G9a/GLP KO OSNs should express multiple ORs at high levels.…”
Section: Discussioncontrasting
confidence: 76%
“…Because perturbations in the OR-elicited feedback result in frequent OR switching but not simultaneous co-expression of multiple OR alleles (Dalton et al, 2013; Lyons et al, 2013), the latter hypothesis is more likely. However, recent theoretical models suggest that singular OR expression could also be explained just by a combination of a slow H3K9 demethylation process and a fast feedback that blocks further demethylation(Tan et al, 2013). In this scenario, removal of the repressive histone marks from a randomly chosen OR allele could be essential and sufficient for OR expression, a hypothesis supported by pharmacological inhibition of G9a/GLP in zebrafish embryos(Ferreira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies have shown that monoallelic OR choice can be modeled with mechanisms similar to those described above, namely OR derepression and the subsequent inhibition of the derepressing mechanism (Alsing & Sneppen 2013, Tan et al 2013). The success of this simple activation–feedback mechanism depends on the ratio between the average time it takes to activate an OR and the time it takes for feedback inhibition to occur (Tan et al 2013). Coexpression occurs if the activation of a second OR occurs shortly after the activation of the first—that is, before feedback inhibition can shut off the derepression mechanism.…”
Section: Chromatin-mediated Silencing Of Olfactory Receptor Genes Ismentioning
confidence: 99%
“…Once a functional OR has been activated, rapid induction of Adenylyl Cyclase 3 provides feedback downregulation of KDM1A, preventing both the activation of other OR genes and downregulation of the OR by repressive KDM1A complexes. This allows for terminal differentiation and locks each individual OSN in a state of sustained expression of a single olfactory receptor ( Figure 3D) [86,87].…”
Section: Kdm1a In the Normal Brain And In Neurodegenerative Diseasementioning
confidence: 99%
“…If the OR is functional, Adcy3 is activated and KDM1A expression downregulated, allowing for the continued expression of that OR. If the OR is not functional, Adcy is not activated and the expression of another OR is attempted [86,87] future science group KDM1 treatments of oncological & neurodegenerative disease Review out that they could not exclude the possibility that the effect was provoked by inhibition of MAOs, which can perturb glucocorticoid receptors in the hippocampus and affect memory consolidation [109]. Indeed, RN-1 was administered as a single high dose which is incompatible with repeated administration [tamara maes, unpublished Data].…”
Section: Figure 3 Feedback Inhibition Mechanisms Of Kdm1a Activity Imentioning
confidence: 99%